PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, CAPITAL INTENCITY DAN PENGUNGKAPAN CORPORATE SOCIAL R ESPONSIBILITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Sektor Perdagangan, Jasa dan Investasi yang Terdaftar di BEI 2013-2016) - Firman Jaya; Zirman Zirman; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The aim of this study are to examine the effect of liquidity, profitability, firm of size, capital intensity and corporate social responsibility disclosure to tax aggressiveness. The independent variables are used in this study are corporate sosial responsibility disclosure, size of firm, profitability, leverage and capital intensity. While the dependent variable in this study is tax aggresiveness the measured using two kind of effective tax rates (ETR). Population taken as the object of observation amounted 90 trading, service and investment companies listed in Indonesia Stock Exchange in the 2013-2016 period. Determination of the sample was made by applying purposive sampling method and obtaining a sample of 92 manufacturing of financial statement companies based on certain criteria. The result showed that the liquidity, profitability and firm of size significant effect on the tax aggresiveness. While capital intensity and corporate social responsibility significantly but negatively influence the tax aggresiveness.Keyword : liquidity, profitability, firm of size, capital intensity and corporate social responsibility and tax aggresivness